The Interferences of Indonesian Grammatical Aspects into English: An Evaluation on Preservice English Teachers’ EFL Learning - Linarsih, Andini; Irwan, Dedi; Putra, Muhammad Iqbal Ripo (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2020)
Decades-long researches in a language in contact field have proved that when a learner learns a new language, his/her knowledge regarding their first language might interfere with their learning. If it occurs, the learning process will be more challenging. The data in this research was collected by using document study technique on twenty-five research outlines written by preservice English teachers in order to investigate the potential of interferences of Indonesian subject – verb agreement pattern into English. To do so, a descriptive study was adopted. The data was analysed by incorporating error and contrastive analyses. The finding of this research confirmed that four types of subject – verb agreements pattern of English had been interfered by that of Indonesian. The grammatically incorrect sentences, which were caused by such interferences, occurred very individually. It means that the interference varies from one preservice English teacher to another.